Pharmacodynamic and pharmacokinetic effects and safety of verinurad in combination with allopurinol in adults with gout: a phase IIa, open-label study. Issue 1 (8th February 2018) - Fleischmann, Roy; Winkle, Peter; Miner, Jeffrey N; Yan, Xiaohong; Hicks, Liz; Valdez, Shakti; Hall, Jesse; Liu, Sha; Shen, Zancong; Gillen, Michael; Hernandez-Illas, Martha
Abstract : Objectives: Verinurad (RDEA3170) is a high affinity, selective uric acid transporter (URAT1) inhibitor indevelopment for treating gout and asymptomatic hyperuricaemia. This phase IIa study evaluated the pharmacodynamics, pharmacokinetics and safety of verinurad combined with allopurinol versus allopurinol alone in adults with gout. Methods: Forty-one subjects were randomised into two cohorts of verinurad (2.5–20 mg) plus allopurinol (300 mg once daily) versus allopurinol 300 mg once daily, 600 mg once daily or 300 mg twice daily alone. Each treatment period was 7 days. Serial plasma/serum and urine samples were assayed for verinurad, allopurinol, oxypurinol and uric acid. Results: Serum pharmacodynamic data pooled across cohorts demonstrated maximum per cent decreases in serum urate (sUA) from baseline (Emax ) at 7–12 hours after verinurad plus allopurinol treatment. Combination treatment decreased sUA in dose-dependent manner: least-squares means Emax was 47%, 59%, 60%, 67%, 68% and 74% for verinurad doses 2.5, 5, 7.5, 10, 15 and 20 mg plus allopurinol 300 mg once daily, versus 40%, 54% and 54% for allopurinol 300 mg once daily, 600 mg once daily and 300 mg twice daily. Verinurad had no effect on allopurinol plasma pharmacokinetics, but decreased oxypurinol Cmax by 19.0%–32.4% and area under the plasma concentration–time curve from time zero to the last measurable time point by 20.8%–39.2%. Verinurad plus allopurinol was well tolerated with no serious adverse events (AEs), AE-related withdrawals or renal-related events. Laboratory values showed no clinically meaningful changes. Conclusion: Verinurad coadministered with allopurinol produced dose-dependent decreases in sUA. All dose combinations of verinurad and allopurinol were generally well tolerated. These data support continued investigation of oral verinurad in patients with gout. Trial registration number: NCT02498652.